Production of Mayonnaise from Corn Oil and Soyaoil Using Skim Milk as Emulsifier - Otitoola, O.C.; Akanbi, C.T. (Ife Journal of Technology, 2011)
The objective of this study was to investigate the use of skim milk as an emulsifier in salad dressings and to compare its chemical, rheological and sensory properties with egg yolk based mayonnaise. Mayonnaises were produced (with or without gum) from corn oil and soya oil using egg yolk or skim milk as emulsifiers. The emulsification capacity (EC) of the emulsifiers, proximate composition, rheological and sensory properties of the mayonnaises were determined. The emulsification capacity was 50 and 57% for skim milk and egg yolk respectively. Addition of 0.2% sodium carboxyl methylcellulose increased the EC to 86 and 90% respectively. Moisture, protein, fat, sugar and starch of the samples were found to be in the range of 17.2-47.7%, 0.4-2.0%, 11.0-70.0%, 1.0-13.0 and 0.4- 6.1%. Egg yolk based dressings were more viscous (216-315Nsm-2) than skim milk based dressings (90-216Nms-2), although all products were found to be pseudo plastic. The results of sensory evaluation showed that egg yolk based dressings were preferred for such quality attributes as smoothness, texture, hand feel and mouth feel. However there was no significant difference (P<0.05) between skim milk based dressings and egg yolk based dressings in terms of taste, colour and flavour.